2007
DOI: 10.1074/jbc.m609756200
|View full text |Cite
|
Sign up to set email alerts
|

A Multicopper Ferroxidase Involved in Iron Binding to Transferrins in Dunaliella salina Plasma Membranes

Abstract: Iron is an essential element for all photosynthetic organisms because it is a cofactor of multiple components in photosynthetic electron transport. Iron deficiency is a common limitation for plant and algae proliferation because of its low availability in aerobic aqueous solutions. On the other hand, an excess of iron is highly toxic because it can elicit the formation of reactive oxygen species causing oxidative damage. Therefore, all photosynthetic organisms had to develop efficient regulatory mechanisms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
(50 reference statements)
0
34
1
Order By: Relevance
“…Another nonreductive iron uptake system involving binding of iron by a surface transferrin-like protein was described in the halotolerant alga Dunaniella salina (Paz et al, 2007a(Paz et al, , 2007b. In this alga, iron deficiency induces primarily iron binding to the cell surface rather than iron internalization (Paz et al, 2007b), which is the opposite of what we observed in C. velia.…”
Section: Discussioncontrasting
confidence: 73%
“…Another nonreductive iron uptake system involving binding of iron by a surface transferrin-like protein was described in the halotolerant alga Dunaniella salina (Paz et al, 2007a(Paz et al, , 2007b. In this alga, iron deficiency induces primarily iron binding to the cell surface rather than iron internalization (Paz et al, 2007b), which is the opposite of what we observed in C. velia.…”
Section: Discussioncontrasting
confidence: 73%
“…Fe-responsive gene in Dunaliella salina encodes a protein thought to associate with plasma membrane transferrins where it functions, along with a multicopper ferroxidase, as part of a complex that enhances binding and uptake of ferric ions (41). However, there is no evidence for the occurrence of genes that encode transferrin in the genome of P. tricornutum.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether iron internalization indeed results from endocytosis of iron-binding proteins, we tagged membrane surface proteins in irondeficient cells with a membrane-impermeable biotin derivative and monitored biotin-tagged proteins labeled with the fluorescein avidin with a confocal microscope. We found that, in iron-deficient cells, biotin tags almost exclusively three protein bands that were identified as the major iron deprivation-induced plasma membrane proteins (Paz et al, 2007): two transferrin-like proteins, TTf (Fisher et al, 1997(Fisher et al, , 1998 and DTf (Schwarz et al, 2003a), and a 130-kD band that was found to contain two proteins, a multicopper ferroxidase, termed DFox, and a second unknown protein. In stained cells that were kept at 4°C, biotin-tagged label was confined to the outer cell surface (Fig.…”
Section: Bound Iron Is Internalized Into Acidic Vacuolesmentioning
confidence: 96%
“…However, the kinetic mechanism has not been investigated and the site of iron internalization was not identified. In a recent study, we found that iron deprivation induces in D. salina a large increase in ironbinding capacity and that this enhanced binding was correlated with accumulation of three additional plasma membrane proteins, which were found to associate with TTf: a second transferrin, termed DTf, a multicopper ferroxidase, termed DFox, and another 130-kD protein (Paz et al, 2007).…”
mentioning
confidence: 92%